2015
DOI: 10.5755/j01.ee.26.5.12463
|View full text |Cite
|
Sign up to set email alerts
|

Highly-Skilled Migration, Migrant Networks and the Prestige of Academic Institutions

Abstract: This research analyzes the connection between highly skilled migration and several determining factors such as migration networks, the prestige of academic institutions and the Gross Domestic Product per capita. The linear regression method has been used to analyze a sample of 207 countries, 25 receiving countries and 182 sending countries from 6 different regions (Africa, Asia, Europe, North America, Central and South America and Oceania). A global analysis including all the countries of the sample and a part… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 35 publications
(68 reference statements)
0
11
0
3
Order By: Relevance
“…Otherwise, they gain the same rights as national population, situation in which a protectionist policy would limit the cost to the host country (Müller, 1997). Mihi-Ramirez et al (2016) and Garcia-Rodriguez et al (2015) consider that there exists a self selection of immigrants in highly developed countries where the greater degree of innovation and the prestige of academic institutions have a positive impact on the arrival of highly skilled immigrants. The impact of immigration in the host country is different from country to country depending on its capacity to integrate immigrants and on many aspects such as the intensity of the phenomenon of immigration, the composition of the group, skills of migrants, their age and relationship with the labour market of the host country, the level of education, reasons for migration, the type of migration, permanent or temporary and the level of development and the host country's ability to integrate waves of immigrants.…”
Section: Immigration Process In European Unionmentioning
confidence: 99%
“…Otherwise, they gain the same rights as national population, situation in which a protectionist policy would limit the cost to the host country (Müller, 1997). Mihi-Ramirez et al (2016) and Garcia-Rodriguez et al (2015) consider that there exists a self selection of immigrants in highly developed countries where the greater degree of innovation and the prestige of academic institutions have a positive impact on the arrival of highly skilled immigrants. The impact of immigration in the host country is different from country to country depending on its capacity to integrate immigrants and on many aspects such as the intensity of the phenomenon of immigration, the composition of the group, skills of migrants, their age and relationship with the labour market of the host country, the level of education, reasons for migration, the type of migration, permanent or temporary and the level of development and the host country's ability to integrate waves of immigrants.…”
Section: Immigration Process In European Unionmentioning
confidence: 99%
“…Por otra parte, es fundamental el papel de las redes en la emigración e inserción y se mantiene como en otros casos un horizonte de retorno más o menos cercano. En la migración de científicos y científicas, las redes son también fundamentales (García-Rodríguez et al, 2015).…”
Section: Las Migraciones Cualificadas Y De Personal Científicounclassified
“…Como cuarta característica, si la alta cualificación denota la relevancia del capital cultural, en términos de Bourdieu (2000), el caso de quienes se dedican a la ciencia representa la relevancia del capital simbólico, tal y como lo entendió el mismo autor (Bourdieu, 1987), en la medida en que se trata de una profesión de prestigio, desarrollada en instituciones altamente valoradas. De hecho, el prestigio de las instituciones académicas constituye un elemento fundamental en la movilidad geográfica en el campo de la ciencia, junto con la existencia de redes (García-Rodríguez et al, 2015). De hecho, una de las cuestiones que afloran en los trabajos sobre migraciones calificadas es la importancia de las cuestiones simbólicas en la decisión de los sujetos para emprender proyectos migratorios (Pastore y Tomei, 2018) que contribuyen a enmarcar los desplazamientos y conexiones que se producen en trayectorias migratorias realizadas desde posiciones de privilegio (Lundström, 2014) o en desplazamientos Norte-Sur que resultan estratégicos para proyectos personales y trayectorias vitales (Amit, 2014).…”
Section: Las Migraciones Cualificadas Y De Personal Científicounclassified
See 1 more Smart Citation
“…migratory flows) has proven to be an effective strategy for reducing the structural unemployment rate, rejuvenating the labour market and increasing the participation rate (Mihi-Ramirez et al, 2019;Miranda-Martel et al, 2017;Gamberoni et al, 2016). It has also been observed that the increase in the number of immigrants plays an important role in the growth of Gross Domestic Product per capita, GDPPC 1 (Garcia-Rodriguez et al, 2015). However, the impact of immigration on productivity varies from country to country (Miranda-Martel et al, 2018;Melchor-Ferrer et al, 2017;Peri, 2016;Kangasniemi et al, 2009).…”
Section: Introductionmentioning
confidence: 99%